Imaginaries, invariant types and pseudo p-adically closed fields - Montenegro Guzmán, Samaria (2019)
In this paper, we give a general criterion for elimination of imaginaries using an abstract independence relation. We also study germs of definable functions at certain well-behaved invariant types. Finally we apply these results to prove the elimination of imaginaries in bounded pseudop-adically closed fields.